Improvement of condensation heat transfer by surface modifications - Leipertz, Alfred; Fröba, Andreas Paul (Heat Transfer Engineering, 2008)
Condensation processes are of importance for many heat transfer applications where a large amount of energy has to be transferred by a working fluid using the latent heat available during the phase transition. Whether ideal dropwise or filmwise condensation or a mixed condensation form can be realized depends on the properties of the heat tran, fer surface. The quantities that mainly influence the condensation form are the surface tension of the condensing fluid, the surface roughness or structure, and the surface energy of the condenser surface. During the past two decades at LTT-Erlangen, experimental and theoretical work has been carried out to reduce the surface energy of common heat transfer surfaces in such a way that stable dropwise condensation can be reached and maintained for extended time periods. In this situation, heat transfer is superior to filmwise condensation for at least one order of magnitude. The methods that have been developed and extensively tested for a selective adjustment of dropwise condensation of water at metallic surfaces are surface coating by diamond-like carbon films (DLC) and ion implantation. For both methods, the principles and fundamental experimental investigations are explained, and for ion implantation, a technical utilization is presented in the form of its application to sea water desalination plants based on mechanical vapor compression.